Motif Batik Tradisional Khas Pangkalan Brandan sebagai Simbol Peristiwa Bumi Hangus Pangkalan Brandan - Maysaroh, Maysaroh; Lestari, Ayu; Siregar, Yusra Dewi (Medan Resource Center, 2024)
This article explores the history of the distinctive batik motifs from Kampong Batik Brandan, which hold unique characteristics and serve as a representation of the